2022
DOI: 10.1002/admi.202201486
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Based Electrocatalysts for Seawater Oxidation

Abstract: Electrocatalytic water splitting is an effective strategy, which can convert intermittent energy such as wind energy and solar energy into renewable and sustainable hydrogen energy. Global freshwater resources are extremely scarce. Compared with freshwater, seawater is a rich and sustainable resource, and it has attracted more and more attention in electrocatalysis. However, the oxygen evolution reaction (OER) is a four‐electron transfer process, which leads to slow reaction kinetics. Moreover, the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Recently, transition metal-based compounds have become an ideal choice to replace precious metal catalysts because of their abundant reserves and adjustable structural properties. , For example, oxides, , hydroxides, , layered double hydroxides (LDH), metal organic frameworks (MOFs), and their derivatives have attracted lots of research interests. Among them, the LDHs are an important kind of two-dimensional layered anionic clay, which consists of positively charged layers (brucite-like M­(OH) 6 octahedron) and anions between layers. LDHs possess many advantages, such as the adjustable chemical composition of layers, easy exchange of anions between layers, structural topological transformation, high specific surface area, etc. ,, As catalysts themselves, catalyst carriers, or catalyst precursors, LDHs exhibit many important applications in photocatalysis and electrocatalysis. , In particular, Co–Mn-based double-layer hydroxide has become one of the most active materials in electrolytic water oxidation because of its low cost and easy control of structure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, transition metal-based compounds have become an ideal choice to replace precious metal catalysts because of their abundant reserves and adjustable structural properties. , For example, oxides, , hydroxides, , layered double hydroxides (LDH), metal organic frameworks (MOFs), and their derivatives have attracted lots of research interests. Among them, the LDHs are an important kind of two-dimensional layered anionic clay, which consists of positively charged layers (brucite-like M­(OH) 6 octahedron) and anions between layers. LDHs possess many advantages, such as the adjustable chemical composition of layers, easy exchange of anions between layers, structural topological transformation, high specific surface area, etc. ,, As catalysts themselves, catalyst carriers, or catalyst precursors, LDHs exhibit many important applications in photocatalysis and electrocatalysis. , In particular, Co–Mn-based double-layer hydroxide has become one of the most active materials in electrolytic water oxidation because of its low cost and easy control of structure .…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, transition metal-based compounds have become an ideal choice to replace precious metal catalysts because of their abundant reserves and adjustable structural proper-ties. 15,16 For example, oxides, 17,18 hydroxides, 19,20 layered double hydroxides (LDH), 21−23 metal organic frameworks (MOFs), 24−26 and their derivatives have attracted lots of research interests. Among them, the LDHs are an important kind of two-dimensional layered anionic clay, which consists of positively charged layers (brucite-like M(OH) 6 octahedron) and anions between layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 3,18–23 ] Moreover, these electrocatalysts need to be engineered and modified in order to maintain high selectivity and chloride corrosion resistance during direct seawater splitting in an alkalized saline electrolyte. [ 2,24–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Fortunately, the activity of a catalyst can be improved by a reasonable strategy for interface-structure design, such as constructing heterojunctions or doping. [26][27][28][29][30] For the first time, Lin et al improved the interfacial activity of Co(OH)F using atomic replacement, which significantly improved the efficiency of oxygen evolution by electrolytic dissolution of water. 31 That work showed that the efficiency of atomic utilization could be high.…”
Section: Introductionmentioning
confidence: 99%